Increasing the somatic embryogenesis frequency of Panax vietnamensis Ha et Grushv. by disinfection of leaf explant using nano silver and the addition of nano silver in culture medium - Cuong, Do Manh; Tung, Hoang Thanh; Dac Khai, Hoang; Quoc Luan, Vu; Thi Hien, Vu; Thi Bich Phuong, Truong; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2020)
Somatic embryo is a developmental method for mass multiplication of valuable medicinal plants. In this study, leaf explants of Ngoc Linh ginseng were disinfected with nano silver at different concentrations and exposure times to eliminate infectious agents and induce embryogenic callus for the production of somatic embryos. The results show that the lowest contamination rate (20.00%) was observed when leaf explants were treated with 0.5 g/L nano silver for 15 minutes while the highest embryogenic callus induction rate (72.22%) and fresh weight (0.77 g) was determined at 0.2 g/L nano silver for 20 minutes. High frequency of somatic embryogenesis formation and germination were occurred on MS medium supplemented 1.0 mg/L 2,4-D; 0.5 mg/L NAA; 0.2 mg/L Kin and 1.6 mg/L nanosilver. After 8 weeks of culture, the number somatic embryos derived from nano silver treated-leaves was increased 2 times than non-treated explants. Addition of 1.0 mg/L NAA and 1.2 mg/L nano silver was showed the highest shoot and root length, root number, fresh and dry weight of plantlets. This research showed that pre-treatment and supplement of nano silver in culture medium is potentially useful for improving embryogenesis frequency, and plantlet formation of Ngoc Linh ginseng cultured in vitro.